Experimental and simulated performance of hot mirror coatings in a parabolic trough receiver. (1st January 2020) - Kaluba, V.S.; Mohamad, Khaled; Ferrer, P.
Highlights: Introducing a hot mirror coating onto the glass cover of the receiver unit. The hot mirror coating reduces the dominant radiant energy losses. The system with hot mirror coating can be used for high temperature applications. First time comparison between hot mirror experiment and simulation. First time simulation of realistic hot mirror systems. Abstract: Thermal radiation is the dominant heat loss mechanism for receiver units on a parabolic solar collector plant at high temperatures. Reduction of these losses is traditionally achieved through the use of an optically selective coating on the absorber pipe, which absorbs visible light well but emits poorly in the IR region. Another possibility is the use of a hot mirror coating on the glass cover of the receiver, which reflects thermal radiation back onto the absorber pipe for reabsorption. In this paper, novel experimental results of a receiver unit operating with a hot mirror coating are presented, and the results between a developed model and a simulation are compared. It is seen that the correspondence is encouragingly close (Chi-squared test p-values between 0.995 and 0.80), where the simulation underestimates the experimental performance. Further, simulations to investigate the performance of various candidates for hot mirror coating (ITO, Gold, and Silver) in a Solar trough receiver are presented, where it is seen that the hot mirror coating has access to higher temperature regions (above 700 K). Lastly, optical parameter variation effects were simulated, related to overall plant efficiency and compared to existing selective coatings.